Pengaruh Perendaman Terhadap Mutu Tepung Sagu (Metroxylon sp.) di Kampung Tambat Kabupaten Merauke - Witdarko, Yus; Jamaludin, Jamaludin; Parjono, Parjono; Pamungkas, Wiyan Afriyanto (Universitas Musamus, Merauke, Papua, 2022)
This study aims to identify the quality of